2021
DOI: 10.1136/emermed-2020-210305
|View full text |Cite
|
Sign up to set email alerts
|

Emergency scalpel cricothyroidotomy use in a prehospital trauma service: a 20-year review

Abstract: BackgroundThis study aimed to determine the rate of scalpel cricothyroidotomy conducted by a physician–paramedic prehospital trauma service over 20 years and to identify indications for, and factors associated with the intervention.MethodsA retrospective observational study was conducted from 1 January 2000 to 31 December 2019 using clinical database records. This study was conducted in a physician–paramedic prehospital trauma service, serving a predominantly urban population of approximately 10 million in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
1
15
0
2
Order By: Relevance
“…All three of these patients sustained severe panfacial fractures with imminent airway obstruction. Similar findings were reported by Aziz et al over a twenty-year period [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…All three of these patients sustained severe panfacial fractures with imminent airway obstruction. Similar findings were reported by Aziz et al over a twenty-year period [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…This 82% success rate is slightly lower than the 90.5% reported in a previous meta-analysis [ 23 ], likely due to the more serious injury profile, and by extension anatomical disruption, in the military patient cohort. In comparison, a review of the last 20 years of experience of London HEMS demonstrated a much lower incidence of only 0.19% (72 of 37,725 patients) with a 97% success rate [ 24 ]. Of interest, penetrating trauma (stabbing of gunshot wound) at any anatomical location, accounted for only 8 (10.3%) cases of scalpel cricothyroidotomy over this 20-year case review.…”
Section: Resultsmentioning
confidence: 99%
“…While surgeons familiar with the technique may prefer to perform rapid tracheotomy in the CVCO situation, 204 in the hands of non-surgeon clinicians, and because of anatomic advantages in adult patients, eFONA should generally proceed via the cricothyroid space. For its simplicity, ease of equipment stocking, generalizability to different airway manager types, and emerging evidence of first-pass success in various settings, 205 , 206 the CAFG recommends a scalpel-bougie-tube approach for cricothyrotomy. If feasible, the neck should be fully extended.…”
Section: Response To An Unsuccessful First (Or Subsequent) Attempt At the Intended Airway Techniquementioning
confidence: 99%